Body Image, Perilaku Makan Dan Faktor Lainnya Dengan Status Gizi Lebih Pada Remaja Putri Di Smk Kesehatan Letris - Oktaviani, Annisa; Yunieswati, Wilda (Jurnal Gizi dan Kuliner, 2023)
This study investigates the relationship between body image, eating behavior, and physical activity with the nutritional status of adolescent girls at Letris 1 Health Vocational School, South Tangerang. The research involved 71 10th-grade teenage girls, and data was collected through a cross-sectional design and simple random sampling technique. Results showed that 23.9% of respondents were overweight and 11.3% obese. The study found a significant relationship between body image, eating behavior, and over-nutrition status. However, there was no significant relationship between protein intake, fat, carbohydrates, physical activity, and overnutrition status. The findings suggest that interventions promoting balanced nutrition and positive body image perceptions should be implemented in schools to encourage good eating behavior and positive body image perceptions among young women. Keywords: Body image, Eating Behaviour, Nutrition Status